Healthcare and Physical Education of Children and Youth in Prague 1869–1914 - Waic, Marek; Pavlů, Dagmar (Frontiers in Sports and Active Living, 2020)
The article focuses on the healthcare and physical education of children and youth in Prague, the capital city of Czech lands, in the period after the Austro-Hungarian compromise of 1867. The legislative framework for children's physical development and healthcare consisted of laws passed by the Imperial Council which were in force throughout the entire region of Cisleithania. Its execution and implementation, however, were the responsibility of the Czech territorial assembly and Prague municipality. The study analyses the environment in which children grew up, the quality of their diet, and their medical care, particularly the activities of school doctors. Further, the text concentrates on the organization and the quality of school physical education. Prague serves as an example of an industrial centre of the Cisleithanian region whose industrial development caused rapid urbanization which limited the possibilities of physical development of children and youth. Until the end of the 19th century, the only possibility of organized exercises was school physical education, and its quality was greatly influenced by the modest spatial conditions of schools. Even at the better-equipped grammar schools, physical education was an optional subject until 1909 and was not taught at most of them at all. As part of the modernization of the empire, the Cisleithanian government supported physical education, also for military reasons. The same was done by the Prague municipality, where care for the physical development and health of children and youth did not become the subject of political disputes.